Child-Protection Systems – Romanian Perspective - Mihăilă, Carmen Oana (Child-Protection Systems, 2025)
Abstract:Children’s rights are fundamental rights with a universal character. Therefore, it is imperative to ensure their protection at a common level not only in the European Union but also globally. Thus, considering the multiple challenges in the field of child protection, the approach must be a crossborder one and not just at the level of each individual member state. In Romania, the child protection system has seen a profound reform in recent years, with a strong emphasis on preventing separation of the child from the family, with the attempt to deinstitutionalise and create an alternative in accordance with the best interests of the child and the family type, with efforts to protect and support children with disabilities. This multifaceted process involves central and local public authorities, NGOs, and community based structures. Despite progress, Romania still faces systemic shortcomings, especially regarding funding and resource allocation. Changes in public policy are required; a correct application of the legislation and specialised personnel are needed; risk situations in which children are found must be quickly identified, including in rural areas; and urgent interventions are needed to protect children without care by choosing the most suitable service. Moreover, children with special educational needs or disabilities remain vulnerable to exclusion due to a persistent lack of adapted infrastructure and support services. Keywords: deinstitutionalisation, special protection services, foster care, placement, guardianship, adoption